Sexual Dysfunction in Premenopausal Women With Obstructive Sleep Apnea - Yilmaz, Zahide; Sirinocak, Pinar Bekdik; Voyvoda, Bekir; Ozcan, Levent (Urology Journal, 2017)
Purpose: Sexual functions in the males with obstructive sleep apnea syndrome (OSAS) have been well investigated in the literature; however sexual functions in the premenopausal women with OSAS have been studied to a lesser extent. Materials and methods: The study included 22 premenopausal women diagnosed as OSAS by the polysomnographic (PSG) evaluation. The control group included 13 premenopausal women suspected of sleep-related respiratory disorder, but whose PSG tests were determined to be normal. Both groups were administered Epworth Sleep Scale (ESS), Beck Depression Scale (BDS), and Female Sexual Function Index (FSFI) questionnaire forms. Relations between disease parameters, and the total FSFI score, and scores of the six FSFI parameter were analyzed. Results: The total FSFI score in the cases with OSAS, was determined to be significantly lower than that of the control subjects (P = .031). Scores of the desire, arousal, and orgasm were determined to be significantly lower in the patient group, compared to control group (P = .034; P = .048; P = .039). The total FSFI scores, and scores of the desire, arousal, lubrication, orgasm, satisfaction and pain subscales in the cases did not correlate significantly with the apnea-hypopnea index (AHI), Non-Rapid Eye Movement 1 (NREM1)%, NREM2%, NREM3%, REM%, the time spent with saturation O2< 90%, minimum oxygen saturation (%), ESS scores, and BDS scores (all P > .05). Conclusion: Women with OSAS experience sexual dysfunction when compared with normal population. Clinical evaluation has to include also the evaluation of sexual life in women.